2021
DOI: 10.1007/s42832-021-0081-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of plant resource inputs on the energy flux of soil nematodes are affected by climate and plant resource type

Abstract: The relative abundance of different components of the soil food web can vary tremendously in response to plant resource inputs. However, little is known about the mechanisms that plant resource regulates the energy fluxes and soil community composition. Here, we experimentally reduced litter and root inputs for two years in China at low-, mid-, and high-latitude forests to explore the effects of plant-derived resource inputs on the nematode energy flux and community composition. Litter reduction at high and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This result can be explained by the dominance of coniferous tree species at a late stage in Changbai, which led to the increase in the litter C:N ratio (Table 2) and thus a significant decrease in litter quality, and this result was in line with some studies that reported the difference in litter quality affected the abundance of microbivorous nematodes, and then potentially altering the composition of the soil nematode communities (Ilieva‐Makulec et al, 2006; Sauvadet et al, 2017). In addition, due to the importance of the litter layer in maintaining soil microenvironments (by moderating fluctuations in soil temperature and moisture) at high latitudes as a result of the relatively slow decomposition rate of litter (Meentemeyer, 1978), litter properties are likely to influence the composition and diversity of nematode communities at high latitudes (Zhao et al, 2021). In Dinghu, soil properties were more closely related to variation in nematode community composition, especially TSP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result can be explained by the dominance of coniferous tree species at a late stage in Changbai, which led to the increase in the litter C:N ratio (Table 2) and thus a significant decrease in litter quality, and this result was in line with some studies that reported the difference in litter quality affected the abundance of microbivorous nematodes, and then potentially altering the composition of the soil nematode communities (Ilieva‐Makulec et al, 2006; Sauvadet et al, 2017). In addition, due to the importance of the litter layer in maintaining soil microenvironments (by moderating fluctuations in soil temperature and moisture) at high latitudes as a result of the relatively slow decomposition rate of litter (Meentemeyer, 1978), litter properties are likely to influence the composition and diversity of nematode communities at high latitudes (Zhao et al, 2021). In Dinghu, soil properties were more closely related to variation in nematode community composition, especially TSP.…”
Section: Discussionmentioning
confidence: 99%
“…The different stages of the forest at the two latitudes were all regionally representative of forests with larger areas and relatively complete preservation (Shao et al, 2019; Zhang et al, 2016). The predominant soil types were Haplic Ferralsol (lateritic red soil) and Mollisol (dark brown soil) in forest ecosystems at low and high latitudes, respectively (Zhao et al, 2021). The characteristics of the different forest successional stages in the two forests are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that species loss due to long-term exposure to high nutrient availability was nonrandom (Zhou et al, 2021(Zhou et al, , 2022 and that the initial biomass increase trend after fertilizer application gradually diminished over time (Isbell et al, 2013;Kimmel et al, 2020;Zhao et al, 2021). Understory species might be severely constrained by light limitation and thus suffered a higher risk of localized exclusion compared with the canopy species (Dickson and Gross, 2013;DeMalach et al, 2017).…”
Section: Effects Of Fertilization and Shade On Plant Community Compos...mentioning
confidence: 99%
“…We also hypothesized that the soil nematode communities in temperate and tropical forest soils would be particularly sensitive to climatic factors. For instance, global warming may lead to an increase in nematode diversity at higher latitudes and a decrease in nematode diversity at lower latitudes because warmer temperatures would be closer to their physiological optima at higher latitudes and closer to their thermal limits at lower latitudes [31].…”
Section: Introductionmentioning
confidence: 99%